The Study Of Communication Medium That Influence Staff Engagement Relationship In Petronas, Malaysia - Azman, Nurul Amira Irfa (UTeM, 2018)
Communicating with the employees regularly helps ensure everyone understands the objectives and goals, as well their place in achieving it. The purpose of this study is to analyze factors affecting communication medium toward staff engagement relationship in PETRONAS. However to promote more effectively is a problem urgent to solve. This study is to make some contribution to staff engagement toward communication mediums. In the other hands, staffs’ attributes differences were also investigated and data were collected from 255 staff PETRONAS, Malaysia. This research were developed some hypothesis and based on “4-I Dimension Model” were proposed a research model about communication medium toward staff engagement relationship. Involvement, interaction, intimacy and influence included in the model. Questionnaire survey was conducted in PETRONAS through online and by hand. Results shows that involvement, interaction, intimacy and influence had a positive influence on communication medium toward staff engagement.. Furthermore, the effect of interaction on communication medium toward staff engagement relationship is significantly greater.